2018
DOI: 10.1186/s12885-018-4461-z
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 activates TLR4/NF-κB signaling to promote lung adenocarcinoma cell proliferation through activating lncRNA-NEAT1 expression

Abstract: BackgroundLung cancer remains the top contributor to cancer-related mortality worldwide. Long non-coding RNAs (lncRNAs) have been reported to participate in normal development and tumorigenesis. LncRNA nuclear enriched abundant transcript 1 (NEAT1) is highly expressed in lung cancer and promotes lung cancer cell proliferation and migration. However, the upstream regulatory mechanism still needs investigation.MethodsIn the present study, we investigated the upstream regulators and mechanisms of NEAT1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 40 publications
7
79
0
Order By: Relevance
“…Mechanistically, upregulation of NEAT1 in GSCs under ADV infection could be attributed to TLR9 activation, and knockdown of NEAT1 was accompanied with an inhibition of STAT3 expression and phosphorylation. This is consistent with several reports showing that NEAT1 promotes cancer progression by enhancing STAT3 signaling [48][49][50] . Therefore, ADV infection likely triggers TLR9/MYD88 signaling, which upregulated NEAT1 and activated STAT3, and activated STAT3 further upregulates NEAT1 to form a positivefeedback loop, and promotes GSCs formation from primary glioma cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mechanistically, upregulation of NEAT1 in GSCs under ADV infection could be attributed to TLR9 activation, and knockdown of NEAT1 was accompanied with an inhibition of STAT3 expression and phosphorylation. This is consistent with several reports showing that NEAT1 promotes cancer progression by enhancing STAT3 signaling [48][49][50] . Therefore, ADV infection likely triggers TLR9/MYD88 signaling, which upregulated NEAT1 and activated STAT3, and activated STAT3 further upregulates NEAT1 to form a positivefeedback loop, and promotes GSCs formation from primary glioma cells.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, transfection of NEAT1 siRNA abrogated the increased levels of STAT3 and phosphorylated STAT3 induced by ADV infection (Figure 6C, 6D, supplementary Figure S4F). These results, in combination with literatures, suggested that NEAT1 is downstream to TLR9-MYD88 and regulates STAT3 46,[48][49][50] .…”
Section: Neat1 Is Associated With Activation Of Tlr-stat Pathway In Gbmsupporting
confidence: 84%
“…5). Lgals3, encoding Galectin-3 that can activate TLR4/NF-κB signaling, was induced peaking at day 3-14 [23].…”
Section: Dampsmentioning
confidence: 99%
“…Nuclear enriched abundant transcript 1 (NEAT1) is a lncRNA transcribed from the diverse endocrinal neoplasia locus [10]. The interaction of lncRNA NEAT1 has been documented in glioma, prostate cancer and lung adenocarcinoma [11][12][13].LncRNA NEAT1 was also suggested as a tumor promotor in OS by several studies [14][15][16].MicroRNAs (miRNAs) are tiny (~ 22 nucleotides) endogenous non-coding RNA molecules which act at the post-transcriptional level and regulate mRNA expression [17]. They are involved in multiple complicated cellular behaviors [18].…”
mentioning
confidence: 99%
“…Nuclear enriched abundant transcript 1 (NEAT1) is a lncRNA transcribed from the diverse endocrinal neoplasia locus [10]. The interaction of lncRNA NEAT1 has been documented in glioma, prostate cancer and lung adenocarcinoma [11][12][13].…”
mentioning
confidence: 99%